Hydrometallurgical processing of spent lithium ion batteries (LIBs) in the presence of a reducing agent with emphasis on kinetics of leaching - Meshram P.; Pandey B.D.; Mankhand T.R. (My University, 2025)
In this study, sulfuric acid leaching was applied to recover lithium, cobalt, nickel and manganese from the cathodic active material of spent LIBs in presence of a reducing agent, sodium bisulfite. The conditions for the dissolution of valuable metals were optimized while varying the parameters such as acid concentration, leaching time, temperature and pulp density. It was found that with 1M H2SO4 and 0.075M NaHSO3 as reducing agent ~96.7% Li, 91.6% Co, 96.4% Ni and 87.9% Mn were recovered in 4h at 368K and a pulp density of 20g/L. Kinetic data for the dissolution of the metals such as Li, Co and Ni in the temperature range 308-368K showed best fit to the kinetic model governed by the empirical logarithmic rate law. Leaching of the metals proceeded through the diffusion of lixiviant on the surface of the substrate particles, which was corroborated by XRD phase analyses and SEM-EDS of the untreated sample and the leach residues. From the leach liquor, >98% Co was recovered as cobalt oxalate (CoC2O4·2H2O) by precipitation with oxalic acid. MnCO3, NiCO3 and Li2CO3 were precipitated from the cobalt depleted solution. By this process, high recovery of Li and Co could be achieved in the solution and then in the form of carbonate and oxalate, respectively along with the recovery of Mn and Ni as their carbonates. © 2015 Elsevier B.V.